Modem information technologies in a foreign language course for the engineering-profile students - Кузнецов, В. О. (Proceedings of National Aviation University (archive), 2021)
The opportunities of usage of modem personal computers and information-communicative technologies closely associated with them (first of all - Internet) for foreign language teaching of engineering s considered. Large possibilities, real prospects and features of practical application of new teaching in special content-based foreign language curricula are discussed, that are based on usage in didactijc the authentic materials directly relevant to technical speciality of students.